A novel (ATC)n microsatellite locus is associated with litter size in an indigenous Chinese pig. Issue 4 (6th May 2021) - Wu, Guofang; Shen, Wenjuan; Xue, Xingxing; Wang, Lei; Ma, Yuhong; Zhou, Jiping
Abstract: Simple sequence repeats (SSRs) are an important part of the genome and have become powerful auxiliary DNA markers in animal breeding using marker‐assisted selection (MAS). Based on previous sequencing data of Qinghai Bamei pigs, a total of three novel candidate SSR loci were analysed in this study. Time‐of‐flight mass spectrometry (TOF‐MS) was used for SSR genotyping, and association analyses between SSRs and the litter size of Qinghai Bamei sows was also performed. The results of genotyping showed that the (ATC)n ‐P1, (AC)n ‐P2 and (AC)n ‐P3 loci had 2, 3 and 18 genotypes, respectively; 2, 3 and 8 alleles were also identified at these loci. Except for the (AC)n ‐P2 locus, the polymorphism information content ( PIC ) values of other loci were greater than 0.25. Association analyses indicated that only the (ATC)n ‐P1 locus was significantly associated with the litter size of Qinghai Bamei sows ( p = .047). Compared to 189‐/189‐ genotype, individuals with the 189‐/195‐ genotype had the senior litter size, which was 9.04 ± 0.21. Our results enrich the data on SSRs in Qinghai Bamei pigs and indicate that (ATC)n ‐P1 is a candidate locus for MAS in the pig industry. Abstract : Three SSRs of Qinghai Bamei sows were identified through TOF‐MS. Among them, the (ATC)n‐P1 locus was significantly associated with the litter size of Qinghai Bamei sows. Meanwhile, 189‐/195‐ was the dominant genotype. These findings provide a scientific basis and theoretical guidance for the subsequent improvement of litter size in Qinghai Bamei pigs.